2020
DOI: 10.1186/s12904-020-00585-2
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality alleviates the burden on family members caring for patients receiving palliative care exclusively

Abstract: Background: Spirituality can give meaning to life, providing support and guidance in complex situations. Despite its importance in palliative care, the role of spirituality for family caregivers of patients under exclusive palliative care has not received enough attention in the literature. We aimed to address the correlation between spirituality and the emotional burden of family members of patients under exclusive palliative care. Methods: This transversal study was conducted in a tertiary private teaching h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 40 publications
2
16
0
2
Order By: Relevance
“…Of these, two studies showed that PWC caregivers with high spiritual wellbeing had better quality of life and lower care burden scores [31,57]. Vigna et al [58] reported that low spirituality increased the emotional burden of caregivers of palliative care patients. Kasapoğlu [59] also reported a negative correlation between spiritual well-being and fear of COVID-19 in the normal population.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, two studies showed that PWC caregivers with high spiritual wellbeing had better quality of life and lower care burden scores [31,57]. Vigna et al [58] reported that low spirituality increased the emotional burden of caregivers of palliative care patients. Kasapoğlu [59] also reported a negative correlation between spiritual well-being and fear of COVID-19 in the normal population.…”
Section: Discussionmentioning
confidence: 99%
“…Isso está de acordo com outros estudos que constataram que a prática religiosa ou mesmo a espiritualidade são capazes de dar sentido à vida do cuidador, agregando resiliência e melhorando seu modo de enfrentamento diante da sobrecarga causada pelo processo de cuidar. 21,22 Além disso, cuidadores divorciados e solteiros podem apresentar menor QV do que cuidadores casados. 9,23 Diante dos resultados deste estudo, podemos supor que o apoio conjugal pode ser capaz de reduzir os impactos da sobrecarga de cuidado.…”
Section: Considerações Socioculturais No Cuidado De Adultos Dependent...unclassified
“…Spiritualists can provide support and guidance in complex situations. The existence of interactions between psycho, social, and spiritual can improve the family's coping ability in dealing with difficult situations such as when they have to carry out their role as caregivers for the elderly (Vigna et al, 2020). Spirituality and religion affect health in several ways including regulation of lifestyle and health behavior, access to social resources such as social relationships and social support, promotion of positive selfperception, methods of coping resources (from stress, grief), and belief in health promotion (Suzanne M. Grieb, Erin Donovan, Jordan J.…”
Section: Religious Coping and Its Application To Strengthen Family Re...mentioning
confidence: 99%